Emotions in the Shadow of Objective Liability: Administrative Environmental Protection from the Perspective of Law and Emotions - Jagodziński, Waldemar (Człowiek i Społeczeństwo, 2026)
This article examines administrative monetary penalties in Polish environmental law through the lens of the Law and Emotions framework. It challenges the dominant view of such sanctions as neutral and technical instruments by arguing that they function as emotionally charged mechanisms of public authority. The analysis shows that strict or quasi-objective liability regimes structurally generate fear, anxiety, and moral stigmatization, shaping compliance not only through rational calculation but also through affective governance. Drawing on a doctrinal-interpretive methodology grounded in interdisciplinary scholarship, the study combines legal analysis of statutory provisions and case law with socio-legal insights into regulation and governance. It argues that administrative monetary penalties, despite being formally classified as non-penal measures, operate as forms of hidden punitiveness that produce predictable emotional responses. These effects support compliance but may also undermine perceptions of proportionality, fairness, and trust, particularly affecting smaller entities. The article concludes that administrative sanctioning should be reconsidered within a broader understanding of proportionality that accounts for the foreseeable emotional impact of sanctions and the need for stronger individualization and procedural safeguards.